2023
DOI: 10.1073/pnas.2220041120
|View full text |Cite
|
Sign up to set email alerts
|

Paf1 complex subunit Rtf1 stimulates H2B ubiquitylation by interacting with the highly conserved N-terminal helix of Rad6

Abstract: Histone modifications coupled to transcription elongation play important roles in regulating the accuracy and efficiency of gene expression. The monoubiquitylation of a conserved lysine in H2B (K123 in Saccharomyces cerevisiae ; K120 in humans) occurs cotranscriptionally and is required for initiating a histone modification cascade on active genes. H2BK123 ubiquitylation (H2BK123ub) requires the RNA polymerase II (RNAPII)-associated Paf1 transcription elongation complex (Paf1C). Through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 75 publications
1
3
1
Order By: Relevance
“…In rtf1∆ conditions, SRAT transcription increases, which is consistent with previous observations of antisense upregulation in fission and budding yeast mutants unable to ubiquitylate H2B. 16,61,62 The absence of notable defects in 4tU-seq completion score, intron accumulation, or antisense transcription upon Rtf1 depletion suggests that H2Bub may not intrinsically impact these phenotypes, although further work will be needed to rule out compensatory effects of removing other Rtf1 functions. In contrast to the rapid H2Bub turnover, H3K4me3, H3K79me2/3, and H3K36me3 persist over the depletion time course, and therefore, we cannot readily attribute the transcription defects observed during acute Paf1C depletion to the global loss of these modifications.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In rtf1∆ conditions, SRAT transcription increases, which is consistent with previous observations of antisense upregulation in fission and budding yeast mutants unable to ubiquitylate H2B. 16,61,62 The absence of notable defects in 4tU-seq completion score, intron accumulation, or antisense transcription upon Rtf1 depletion suggests that H2Bub may not intrinsically impact these phenotypes, although further work will be needed to rule out compensatory effects of removing other Rtf1 functions. In contrast to the rapid H2Bub turnover, H3K4me3, H3K79me2/3, and H3K36me3 persist over the depletion time course, and therefore, we cannot readily attribute the transcription defects observed during acute Paf1C depletion to the global loss of these modifications.…”
Section: Discussionsupporting
confidence: 87%
“…We found that the acute depletion of any Paf1C subunit does not lead to the upregulation of antisense transcripts (Figure 2E), suggesting that Paf1C is not directly or solely responsible for preventing their expression. H2Bub has also been implicated in the repression of antisense transcription, 16,61,62 but despite the striking loss of H2Bub upon depletion of Rtf1, we see no significant upregulation of SRATs. These results suggest that Paf1C and likely H2Bub do not intrinsically repress antisense transcription.…”
Section: Long-term Absence Of Paf1c Subunits Upregulates Antisense Tr...contrasting
confidence: 60%
See 2 more Smart Citations
“…Studies have implicated Paf1C in chromatin modifications and epigenetic control through direct contacts with related factors, including FACT [226,227] and Chd1 [228,229]. Additionally, Paf1C has been associated with the maintenance of several histone marks for active chromatin, further emphasizing its role as an important regulator of Pol II productive elongation [229][230][231][232].…”
Section: Elongationmentioning
confidence: 99%